PREVALENCE OF IRIDOVIRUS AND VIRAL NERVOUS NECROSIS IN CANTANG GROUPER (Ephinephelus fuscogottatus x Ephinephelus lanceolatus) - Alfianti, Fadia Tantri; Wahyudi, Dzikri; Kusuma, Prasetya Wahyu; Wibowo, Wahyu Budi; Prabowo, Guntur; Suhermanto, Achmad (Politeknik Kelautan dan Perikanan Dumai, 2024)
Cantang grouper is a leading commodity, especially hatchery centers, namely East Java and Bali which is Indonesia's flagship. The growth of cantang grouper fish is hampered by one of the diseases caused Iridovirus and Viral Nervous Necrosis (VNN). These two diseases attacks the seed stage which causes high mortality, so that early detection is needed for preventive action. This study aims to detect and inventory of Iridovirus and VNN in cantang grouper. This research was carried out at BPBAP Situbondo, Irodovirus was detected using conventional PCR and VNN using rRT-PCR. Cantang grouper samples measuring 2,5-12 cm came from Situbondo and its surroundings, Bali and Lombok with a total of 23 samples. The test results showed that all samples were negative for Iridovirus, while the VNN examination showed 3 positive samples and 20 negative samples. Observation of clinical symptoms showed that the cantang grouper were in good health, swimming actively and did not show symptoms of Iridovirus and VNN infection. The prevalence of VNN infection in cantang grouper 13,04% which was included in the category of frequent infections.